Joseph Trumbull papers - Trumbull, Joseph, 1737-1778.
True copy of a congressional resolution (1776 December 26) signed by John Hancock empowering Joseph Trumbull as commissary general to acquire flour and the ships with which to transport it from Virginia and other southern states, followed by a copy of an order by Trumbull to Jeremiah Wadsworth and an order by Wadsworth to Peter Colt for the acquisition of ships.
Delegate to U.S. Continental Congress, Connecticut public official, and Army officer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Colt, Peter, -- 1744-1824.; Hancock, John, -- 1737-1793.; Wadsworth, Jeremiah, -- 1743-1804.; United States. -- Continental Army. -- Commissary General's Department; United States. -- Continental Army -- Supplies and stores; United States. -- Continental Congress; Flour; Ships; Southern States -- History -- Revolution, 1775-1783.; United States -- History -- Revolution, 1775-1783.; Virginia -- History -- Revolution, 1775-1783.; Army officers; Delegates, U.S. Continental Congress -- Connecticut; Public officials -- Connecticut